Magistral drugs in hospitalized newborns and children - Agueda Cabral de Souza Pereira; Elaine Silva Miranda; Selma Rodrigues de Castilho; Débora Omena Futuro; Lenise Arneiro Teixeira; Geraldo Renato de Paula
Abstract Objective: Study the use of magistral oral solutions and suspensions in infants and children at a university hospital. Methods: This is a descriptive study based on the analysis of the assessed hospital's magistral drug request forms regarding the patients in the neonatal ICU, Obstetrics, Pediatrics and Pediatric Emergency from January 2012 to December 2013. The frequency of drug requests and dispensation was evaluated and the consumption of each active ingredient of the preparations was expressed as number of "infant defined daily dose" (iDDD) and of iDDD/100 bed-days. Results: A total of 657 forms were analyzed - a monthly average of 27 pediatric preparations. The neonatal ICU accounted for 69.6% of these requests. Twenty-one drug items were used, of which the most common were folinic acid (88 requests), sulfadiazine (85) and captopril (73). The consumption of the active principle in these preparations varied in number of iDDD, from 7.5 (hydralazine) to 16,520.0 (folic acid), and in number of iDDD/100 bed-days in the neonatal ICU, from 0.1 (zinc sulfate) to 146.1 (folic acid). Conclusions: The constant consumption of magistral oral solutions and suspensions by newborns and children of the assessed hospital indicates the need for such preparations as a pediatric therapeutic alternative in this hospital.